MANAJEMEN SARANA PRASARANA SEBAGAI UPAYA OPTIMALISASI OUTPUT LEMBAGA PENDIDIKAN ANAK USIA DINI - Ariyati, Tatik; Labib Sajawandi; Luluk Maktumah; Nafa Dwi Yudianita; Farah Maria Reviona; Aulia Anastasya Putri Pramuditya (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2025)
This research is motivated by the lack of a planned management strategy in kindergarten education, resulting in suboptimal educational output. Given that infrastructure management is crucial for improving the quality of early childhood education services, including institutional output, the author chose field research, employing a descriptive qualitative approach, at Nurul Fatah Kindergarten, Kalibaru, Banyuwangi. Data collection involved interviews, observation, and documentation. The results indicate that: Infrastructure management at Nurul Fatah Kindergarten is optimally managed. This includes procurement, utilization, and maintenance, which ensures proper care and maintenance of the infrastructure, resulting in the institution's expected quality output